Узгоджена генетична, біогеографічна та морфологічна диференціація у еволюційно молодих видів: аналіз групи Microtus ''arvalis'' (Mammalia) - Загороднюк, І.В. (Видавничий дім "Академперіодика" НАН України, 2007)
Three levels of differentiation in a group of sibling-species are compared: cytogenetical, biogeographical, and craniometrical ones. Analysis of this problem was carried out on the East-European populations of superspecies Microtus ''arvalis'' which is represented by 3 species: M. arvalis, M. levis, and M. obscurus. On the base of all data, species M. levis demonstrates the features of the oldest species of this group with the most ancestral karyotype, widest zone of sympatry with two other species of this group, and most expressed morphological differences from other species. Totally, using all features, the most clear differences are in the pair levis — arvalis, what was expected for the phylogenetically most distant species of this superspecies group (oldest and youngest species). Thus, the correspondence between levels of cytogenetical, biogeographical, and craniometrical differentiation of the investigated species group is present.